Report of a case with a spontaneous mesenteric hematoma that ruptured into the small intestine. (2016) - Shikata, Daichi; Nakagomi, Hiroshi; Takano, Atsushi; Nakagomi, Takahiro; Watanabe, Hideki; Maruyama, Masahiro; Nakada, Haruka; Yamamoto, Atsushi; Furuya, Kazushige; Hada, Masao; Miyasaka, Yoshiaki; Omata, Masao; et al.
Highlights: This article reports an extremely rare case of spontaneous mesenteric hematoma that ruptured into the jejunum. The etiology of this condition was not revealed by detailed pathological examinations. Abstract: Introduction: A spontaneous mesenteric hematoma is a rare condition. Furthermore, it is extremely rare that the mesenteric hematoma caused gastrointestinal bleeding with an unknown etiology. We experienced a case with a spontaneous mesenteric hematoma that ruptured into the jejunum. Presentation of case: A 75-year-old man was referred to our hospital because of anal bleeding and anemia. Abdominal computed tomography (CT) showed a low density mass measuring 3.0 cm in diameter, including an enhanced spot. This finding suggested that a pseudo-aneurysm or mesenteric hematoma caused active bleeding into the jejunum. He underwent emergent laparotomy and partial resection of the jejunum and the mesentery including the tumor. A histological examination of the jejunum indicated no pathogenic findings causing active bleeding. And there were no findings suggesting the mesenteric aneurysm had developed. The patient had no history related to the development of a mesenteric hematoma, such as trauma, labor, surgery, or anticoagulant treatment. Therefore, we finally diagnosed that a spontaneous mesenteric hematoma had ruptured into the jejunum. Discussion and conclusion: We reported extremely rare condition that the mesenteric hematoma was developed and ruptured into the jejunum without definitive etiology.